2023
DOI: 10.2106/jbjs.rvw.23.00071
|View full text |Cite
|
Sign up to set email alerts
|

Modern Patellofemoral Arthroplasty

Elizabeth C. Bond,
Taylor P. Stauffer,
Stephanie Hendren
et al.

Abstract: Introduction: The ideal procedure for isolated patellofemoral arthritis is a controversial topic. Patellofemoral arthroplasty (PFA) is an option that aims to restore normal kinematics to the knee while preserving bone. PFA has been shown to have benefits compared with total knee arthroplasty (TKA) in this patient population but has historically had a high failure rate. Revision rates are improving with modern implants and tight indications but still remain higher than TKA. This review summarizes cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…It can be considered a bridging surgery for younger patients until they require conversion to TKA. Bond et al’s recently reported that the new third-generation implants showed great promise, with outstanding functional outcomes and a significantly lower risk of mistracking and implant problems [ 84 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…It can be considered a bridging surgery for younger patients until they require conversion to TKA. Bond et al’s recently reported that the new third-generation implants showed great promise, with outstanding functional outcomes and a significantly lower risk of mistracking and implant problems [ 84 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%